2018
DOI: 10.1210/jc.2018-00475
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Levothyroxine Reduces Intrahepatic Lipid Content in Patients With Type 2 Diabetes Mellitus and NAFLD

Abstract: This study demonstrated the efficacy and safety of low-dose TH therapy for NAFLD in men. TH or TH analogs may be beneficial for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 37 publications
6
64
0
2
Order By: Relevance
“…Given these potentially beneficial effects on lipid metabolism, it is possible that thyroid hormone analogues or mimetics could be useful for the treatment of metabolic diseases involving the liver, such as dyslipidemia and NAFLD (9,35). In a recent phase 2b single arm trial, it has been reported that low dose levothyroxine significantly reduced hepatic fat content (assessed by magnetic resonance spectroscopy) in euthyroid patients with type 2 diabetes and NAFLD (40). A multicenter, double-blinded, randomized, placebo-controlled phase 2 trial is also ongoing to evaluate the efficacy and safety of MGL-3196 (i.e., a highly selective liver-directed, thyroid hormone receptor-b agonist) in patients with biopsy-proven NASH.…”
Section: Figmentioning
confidence: 99%
“…Given these potentially beneficial effects on lipid metabolism, it is possible that thyroid hormone analogues or mimetics could be useful for the treatment of metabolic diseases involving the liver, such as dyslipidemia and NAFLD (9,35). In a recent phase 2b single arm trial, it has been reported that low dose levothyroxine significantly reduced hepatic fat content (assessed by magnetic resonance spectroscopy) in euthyroid patients with type 2 diabetes and NAFLD (40). A multicenter, double-blinded, randomized, placebo-controlled phase 2 trial is also ongoing to evaluate the efficacy and safety of MGL-3196 (i.e., a highly selective liver-directed, thyroid hormone receptor-b agonist) in patients with biopsy-proven NASH.…”
Section: Figmentioning
confidence: 99%
“…From a clinical point of view, this present nding suggests the assessment of the fT3/fT4 ratio should be included in the multidisciplinary baseline assessment of patients with NAFLD, and that decreasing the fT3/fT4 ratio may be a promising potential therapy for curing NAFLD or preventing progression. Several studies 33,34 had demonstrated a bene cial effect of low dose Levothyroxine replacement therapy on NAFLD with a decrease in the prevalence of NAFLD and serum liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…(2) A clinical study in diabetic Asian male patients with hepatosteatosis found that low-dose levothyroxine (T 4 ) supplementation for 4 months significantly decreased hepatic fat content, as measured by magnetic resonance spectroscopy. (6) Recently, thyromimetics that target the liver and/or the main TH receptor (THR) isoform in the liver, THRβ, have been developed to prevent and/or treat hepatosteatosis and NASH (2) and have less thyrotoxic effects, such as atrial arrhythmias or osteoporosis, attributable to their selectivity for the THRβ versus THRα isoform. (2) Two promising thyromimetic compounds, VK2879 and MGL-3196, are being studied for their effects on hepatosteatosis, inflammation, and fibrosis in NASH (VOYAGE/NCT04173065 (7) ).…”
Section: Thyroid Hormones and Thyromimetics: A New Approach To Nonalcmentioning
confidence: 99%
“…We have observed that hepatic DIO1 mRNA and activity decrease in late-stage NASH, leading to decreased intrahepatic T 3 concentration. (6) Thus, it is possible that low-dose levothyroxine (T 4 ) may be effective to treat hepatosteatosis and early NASH, (6) whereas low-dose T 3 or thyromimetics that do not undergo DIO1 deiodination may be more useful for later stages of NASH. Finally, given that NASH is a complex disease involving the liver, macrophages, and stellate cells, it is possible that THs or thyromimetics could be combined with other drugs that impact other mechanisms of NASH, such as fatty acid synthesis or inflammation, to achieve even better clinical results.…”
Section: Thyroid Hormones and Thyromimetics: A New Approach To Nonalcmentioning
confidence: 99%